A critical assessment of the impact of the amendment to section 25B of the Income Tax Act, no. 58 of 1962, on natural person non-resident income beneficiaries of South African resident trusts - Galloway, Robin John (Rhodes University, 2026)
In 2023, section 25B of the South African Income Tax Act, No. 58 of 1962, was amended by the insertion of the words “who is a resident”, which resulted in the “conduit pipe” principle only applying to resident beneficiaries. The effect of this is that trustees can no longer vest income for tax purposes in non-resident beneficiaries. The primary aim of the research was, therefore, to critically evaluate whether, as claimed by the South African National Treasury, Article 1(2) of the OECD Model Tax Convention on Income and on Capital (2017) and Article 3(1) of the Multilateral Instrument will provide relief to non-resident beneficiaries of South African resident trusts from economic double taxation resulting from the 2023 amendment to section 25B of the Income Tax Act. To achieve this aim, a literature review was undertaken to describe the tax treatment of trusts and parties to trusts in South Africa, prior to and after the amendment. Thereafter, a hypothetical simulation was used to illustrate the total economic impact of the amendment on natural person non-resident beneficiaries. The simulation involved the distribution of several types of income and capital gains by a South African discretionary trust to three natural person beneficiaries resident in the United Kingdom, Australia, and the Netherlands, respectively. The simulation evaluated the total economic taxation payable directly and indirectly by each non-resident beneficiary before and after the amendment to section 25B of the Income Tax Act in both South Africa and their respective countries of residence to test the validity of the claim by the South African National Treasury. The research was undertaken using a doctrinal methodology, situated within the interpretivist paradigm, where a combination of qualitative and comparative data analysis techniques was used to analyse publicly available documentary data. Detailed calculations were performed based on the simulation, together with the assumptions made for this purpose. The findings of the research revealed that the domestic tax treatment of amounts distributed by a South African resident trust can differ greatly from country to country, which could lead to economic double taxation in certain instances, notwithstanding the relevant Double Tax Agreement, the OECD Model Tax Convention and the Multilateral Instrument. The South African National Treasury’s claim that the effect of Article 1(2) of the OECD Model Tax Convention and Article 3(1) of the Multilateral Instrument would be that nonresident beneficiaries would be provided relief from economic double taxation arising from the South African tax paid by the South African resident trust, was shown not to be correct in every circumstance.
Keywords: Double taxation (http://id.loc.gov/authorities/subjects/sh85132863); Income tax (http://id.loc.gov/authorities/subjects/sh85064772); Trusts and trustees--Taxation (http://id.loc.gov/authorities/subjects/sh85138271); Beneficiaries (http://id.loc.gov/authorities/subjects/sh94001664); Multilateral instrument; OECD Model Tax Convention (https://www.wikidata.org/wiki/Q129729408)